Analysing the Internet and the Public Sphere: The Case of Womenslink - O'Donnell, Susan (Javnost-The Public, 2001)
This article analyses alternative media on the Internet media forms produced by social movements and grassroots groups. A framework for analysing alternative media on the Internet is devised using a wide range of theoretical literature, in particular theories of the public sphere and of social movements. Within a public sphere context, alternative media on the Internet could offer an alternative to mass media by using different production practices, such as those fostering capacities for reflection on the experiences of media audiences. Within a social movement context, alternative media on the Internet could help movement actors reach their political aims, or help maintain a movement by supporting alternative forms of selfunderstanding, friendship networks and communities. Empirical research using the framework was conducted over a two-and-a-half year period on the Womenslink mailing list that linked women.s organisations in Northern Ireland and the Republic of Ireland. The findings contribute to further understanding of the Internet and the transnational public sphere.